Advancements in Sensors and Controllers in Mechatronic - Pratap Singh Bhati, Prem; Singh Rajpurohit, Vikram; Jaiman, Praveen (International Journal of Computer Sciences and Engineering, 2025)
Mechatronics is the synergistic combination of mechanical engineering, electronics, controls engineering, and computers, all integrated through the design process. The cost-effective incorporation of electronics, computers, and control elements in mechanical systems requires a new approach to design. Technical systems, be they small consumer or medical devices or large production processes, increasingly employ electronics and computers to give the final product or system the desired properties. Driving factors are e.g. functional and quality demands, energy utilization, environmental demands, or cost reductions. A striking example of this development can be found in the automotive area – the modern passenger car depends on the integration of the car’s mechanical subsystems with a substantial amount of embedded computers, sensors, actuators, and communication devices. In mechatronics, generally the objectives are to automate a process or to control parameters of system.